Environmental Jurisprudence and the Supreme Court - "Sahu,Geetanjoy" (New Delhi, 2014)
Since the 1980s, the Supreme Court of India has intervened regularly in cases involving environmental issues, taking both state and private actors to task on environmentally destructive actions and policies and asserting itself in the implementation of its judgments. It has thus earned itself a widespread and formidable reputation as a 'green court'. The current volume examines how 'green' the Supreme Court actually is and what it even means to be green in an Indian context. It examines the various kinds of environmental discourse prevalent in India and analyses how these feature in the Supreme Court's judgments. It describes the range of legal and extra-legal factors that affect judicial decision making. It analyses trends and patterns in the Supreme Court's decisions in environmental cases and also points out and explains the contradictions in these patterns. It explores the significant role that the Supreme Court has come to play in implementing its own decisions in environmental cases. It examines the efficiency of such implementation and also considers the question of whether or not it constitutes judicial overreach. It concludes with a reflection on the evolution of environmental jurisprudence in India and the lessons that the newly instituted National Green Tribunal can glean from the Supreme Court's role in environmental cases.
Keywords: India-Supreme Court